POSTVENTA SERVICE AS A STRATEGY FOR THE GROWTH OF COMMERCIAL COMPANIES IN THE MOTORCYCLE RUBRO - Esteban Torres Giménez, Juan; Adán Galeano Meira, Fredy; Román Ayala, Esther; Rosa Trinidad de Ferreira, Nidia (Revista Gênero e Interdisciplinaridade, 2022)
In this final work, “whose objective is: To analyze the development of the post-sale service as a strategy for growth in commercial companies in the motorcycle sector. to the managers of the different commercial companies of the motorcycle department and a survey to the customers, using a survey with 10 questions. The answers were used to identify the aftersales services used by the companies and the benefits of implementing them, the disadvantage of those that are exposed to the commercial companies that do not use this service and finally to find out the benefits that await customers to be loyal to one brand a company, with the research hecha and the results obtained, it is concluded that most companies use the post-sale service as a strategy for customer growth and among the most mentioned are: keep in touch with customers, reports and special offers and guarantee for the purchased product.